Relationship between work fatigue and manual dexterity in dental professionals: observational study: . - Sartorio, Francesco; Ferriero, Giorgio; Corna, Stefano; Dal Negro, Francesca; DeAngeli, Mario; Cudazzo, Andrea; Vercelli, Stefano (La Medicina del Lavoro, 2020)
Background: Neuro-muscular fatigue (ANM) in the upper limbs can cause impaired coordination and dexterity. The main purpose of the study was to investigate whether ANM induced by a working day produced a reduction in digital dexterity in a population of dental health workers (OSD). Secondary objective was to investigate whether there were relationships between any reductions in dexterity and independent socio-demographic variables (gender, age and profession). Methods: A cohort of OSD was assessed before and at the end of a working day of at least 7 hours using the Functional Dexterity Test (FDT). The effects of ANM (time), of the tested limb (dominance), and of their interaction on dexterity were investigated using two-way ANOVA. A multiple linear regression model was applied to explore the relationship between dexterity performance and independent variables. Results: A total of 50 OSDs were included. The net time of the FDT at the end of the day was always higher than in the morning. The ANOVA showed a significant difference for time (p